التحليل الطبقي للمجتمع الجزائري: الإمكانات و الحدود - بوداود, سالم (University of Eloued جامعة الوادي, 2016)
النظرية الماركسية هي نتاج لظروف إقتصادية و إجتماعية و سياسية و ثقافية خاصة بمرحلة تاريخية معينة.و نتاج لمجابهات و تفاعلات مع النظريات والأفكار السائدة آنداك.ففرضت تحليلاتها من خلال الطبقات الإجتماعية على المجتمعات الصناعية الغربية.لما كانت تملكه من إمكانات نظرية و تحليلية و نقدية للأبنية الإجتماعية و مشكلاتها الإجتماعية. و حتى أن السوسيولوجيين الجزائريين استخدموا مفاهيم الطبقة العاملة ، و البورجوازية في تحليلاتهم للطبقات في المجتمع الجزائري.إلا أنه في وقتنا الحاضر نشهد تراجعا للماركسية كمرجعية فكرية في تحليل المجتمعات الغربية المعاصرة، و المناداة بالتخلي عنها و بأدواتها التحليلية. فنتساءل إذن : عن الظروف و الشروط التي نستخدم فيها مفهوم الطبقة الإجتماعية ؟ و كيف تعاملت بعض الدراسات و الأبحاث السوسيولوجية الجزائرية مع مفاهيم الطبقات الإجتماعية؟ و هل بالفعل أن التمايز الإجتماعي من خلال الطبقات الإجتماعية غير ملائم و تجاوزه الزمن في معالجة المجتمعات المعاصرة ؟ ، و ياترى ماهي دواعي تراجع و ضعف استخدامات مفاهيم التحليل الطبقي ؟ the marxist theory is the product of social conditions and the economic,political and cultural-specific historical stage.And the product of its confrontations and interactions with various ideas and theories which were prevailing.this theory imposed its Analysis through the concept of social classes which were applied to industrialised societies ,Moreover the marxist theory contains a great theorical and analytical and critical potentialities for comprehending social stractures and its problems. And even the Algerian researchers use the concepts of working class, the bourgeoisy in their analysis of class in the algerian society. But we witness at this time a decline of marxist theory as an intellectual reference in analysing contemporary western societies, beside the call for the abandoment of analytical tools. So we التحليل الطبقي للمجتمع الجزائري أ. بوداود سالم 74 wonder in this intervention :- what are the cnditions which allow us to use the concept of social class? – how the algerian studies dealt with the concepts of working class, and the bourgeoisie. ? - is it already thalk social diffirentiation through social classes inapropriate and out dated in dealing with contemporary societies. ?.- I wonder what are the raisons of decline and weakness of the usent of class analysis ?
CLASS Analysis in the Algerian Society: the possibilities and boundaries
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الطبقة الإجتماعية ، التراتب الإجتماعي ، الفئات الإجتماعية المهنية; social classes, social stratification, social categories